PENGARUH PENGHARGAAN TERHADAP KINERJA PEGAWAI PEMASYARAKATAN DI LEMBAGA PEMASYARAKATAN KELAS IIA BINJAI - Lubis, Rezky Abadi; Rifani, Denny Nazaria (Journal of Management Small and Medium Enterprises (SMEs), 2024)
The purpose of this study was to examine and analyze the effect of rewards on the performance of correctional employees at the Class II A Binjai Correctional Institution. This research uses quantitative methods with a descriptive approach through primary and secondary data sources. The results showed that giving rewards to employees affected the performance of correctional employees at the Class IIA Binjai Correctional Institution. Keywords: Reward; Performance; Employee; Correctional